THE MAGNIFICENT SEVEN ETIKA BISNIS AL-GHAZALI (Relevansi Etika Bisnis al-Ghazali dengan Dunia Bisnis Modern) - Hafidz Makshum (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
There is no specific discussion regarding business ethics al-Ghazali discussed it intensely. However, this is not an indicator that he is does not leave room for business ethics. Quite the opposite, touches Business ethics in al-Ghazali's study feels very rich to be explored. By Therefore, this article seeks to find points of intersection or the relevance of al-Ghazali's business economic thinking to the business world modern. There are seven things that can be found in al- Ghazali, namely (a) positive motives and intentions in doing business; (b) business is fardhu kifayah; (c) balance of world and hereafter orientation; (d) not greedy in business; (e) greed in business widens the gap between the rich and poor so that it is prone to causing conflict; (f) professionalism; (g) proper behaviour.